Attraction and sexual call in Prodiplosis longifila (Diptera: Cecidomyiidae): Evidence of a sexual pheromone - Erazo, Santiago; Leiton, Francisco; Díaz, Angie; Diaz, Valentina; Angel, Juan Fernando; Achipis, Jan Carlos; Manzano, Maria R. (Revista de Biología Tropical, 2024)
Introduction: Prodiplosis longifila Gagné is a key pest of tomato in Colombia, Ecuador, and Peru. Using a sex pheromone could be an efficient alternative for its monitoring and control, but its presence is unknown. Objective: To determine whether virgin females perform sexual calling and whether confined virgin females attract males. Methods: In the laboratory, 233 individual virgin females were observed between 5:00-20:30 h using a 60X magnifying glass, and the sexual call was determined by extrusion of the ovipositor. Ten virgin females were confined in 43 cm3 containers with tulle lids and coated with petroleum jelly to trap males (n = 16). Both containers were placed equidistantly on the upper inner side of a metal cage with tulle (2 400 cm3) where 10 males were released. The experiment was repeated with 20 confined females (n = 20). In both experiments, the number of attracted males was counted 12 hours later. In tomato crops, two Jackson traps were impregnated with odorless glue from which hung a 43 cm3 plastic container with tulle containing 19-34 virgin females (n = 15). The control containers had no females. Adult resting sites in the field were searched for. Results: P. longifila females performed sexual calling during the scotophase and that containers with females attracted more males than the control. In the field, the attraction was greatest 12 hours after the experiment was set up. At field P. longifila adults are active during the scotophase and rest during the photophase mainly on certain plants. Conclusions: The results indicate that virgin females of P. longifila perform sexual calling and strongly suggest that females release a sex pheromone.